Fractional recovery of proteins and carbohydrates from secondary sludge from urban wastewater treatment plants - Angel Alejandro Filipigh; Elena M. Rojo; Andrea Natalia Pila; Silvia Bolado (Chemical Engineering Journal Advances)
The secondary sludge of wastewater treatment plants is an abundant and problematic bacterial biomass that accumulates nutrients from wastewater, mainly as proteins and carbohydrates. Recent studies have focused on energy recovery of this biomass by anaerobic digestion to produce biogas. However, fractional recovery of the sludge components could increase its value and provide the basis for a biorefinery based on this waste. Since ≈ 40-60% of the bacterial dry weight is protein, this biomass could be an important source of functional peptides or amino acids, and the carbohydrates could be used to produce bioplastics or biofuels. This study compares chemical, physical and biological hydrolysis methods and their sequential and assisted combinations to recover proteins and carbohydrates from sludge. Ultrasound-assisted alkaline treatment provided the highest protein solubilization yield (97.2%) with low degradation, resulting in peptide recovery yields of 75.1% with sizes from 70-215 kDa, 40% of essential amino acids and purity of 35.3% with NaOH 1M. The hydrothermal-alkaline combination almost completely solubilized the proteins but not the carbohydrates (77.4%) with high degradation (52.6%). The hydrothermal-acidic combination achieved high carbohydrate solubilization (94%) and recoveries of glucose (63.6%) and xylose (12.6%) but low protein recovery (43.7%) as small size peptides.